Road-Based Routing Protocol for Vanet Using Sumo and Move - Devipriya, D; Muruganandam, A (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Ad Hoc Network (VANET) is a form of Mobile Ad Hoc Networks (MANET). The field of VANETs started gaining attention in 1980s and it has been an active field of research and development. VANETs provide us with the infrastructure for developing new systems to enhance drivers’ and passengers’ safety and comfort. There are many routing protocols that have been proposed and assessed to improve the efficiency of VANET. Simulator tool has been preferred over outdoor experiment because it is simple, easy and cheap. In this paper, simulation of one of the routing protocols i.e. AODV is done on simulators which allow users to generate real world mobility models for VANET simulations. The Simulation of Urban Mobility (SUMO) and MObility model generator for VEhicular network tools used. MOVE tool is built on top of SUMO which is an open source micro-traffic simulator. Output of MOVE is a real world mobility model and using the simulation of Network Simulator tool and then graphs were plotted using Trace Graph for evaluation. Based on the simulation results obtained, the performance of AODV is analyzed and compared with different node density i.e. 5, 10, 15 and 20 with respect to various parameters like Throughput, Packet size, Packet drops, End to End delay etc.